Colpomenia sinuosa extract mitigates lead acetate-induced testicular dysfunctions in male rats - Almutairi, Layla A.; Abu-Almakarem, Amal S.; Al-Sowayan, Noorah Saleh; Alkhodair, Sahar Abdulrahman; Albishi, Hayat M.; Eid, Thamir M.; Alshanbari, Fahad A.; Abuzinadah, Najlaa Yousef; Mobasher, Maysa A.; El-Said, Karim Samy (Frontiers in Molecular Biosciences, 2025)
BackgroundColpomenia sinuosa brown alga contains pharmacologically active compounds with a wide spectrum of bioactivities; however, few studies have been conducted in the Mediterranean to assess their effects against heavy metal toxicity. One common non-biodegradable contaminant that poses a serious risk to human health and the environment is lead (Pb). This study investigated the efficacy of C. sinuosa extract (CSE) treatment on testicular injury caused by lead acetate (PbAc) in rats.MethodsThe phytochemical, GC/MS profiling, and metal chelation ability of CSE were evaluated. Molecular docking studies were performed using AutoDock Vina. The oral LD50 of CSE was determined by probit analysis. 40 male rats were used as follows: Gp1 as a negative control; Gp2 was treated with 1/10 of CSE LD50 (340 mg/kg b. wt.); Gp3 was administered PbAc solution (100 mg/kg b. wt.); Gp4 was orally administered PbAc as in Gp3 and CSE as in Gp2. All treatments were given daily by gastric tube for 30 days. Body weight changes, biochemical, molecular, and histopathological examinations were investigated.ResultsThe results demonstrate that CSE exerted a pronounced metal-chelating activity in vitro and contain promising phytochemicals. The LD50 of CSE was 3,400 mg/kg b. wt. PbAc-treated rats reported significant testicular dysfunction with impaired semen analysis, biochemical, molecular, and histological changes. CSE treatment showed significant palliative effects on these dysfunctions via improvements in antioxidant status, anti-inflammatory properties, and histopathological alterations. Interestingly, CSE treatment modulates the JAK2/STAT3, and NLRP3/Caspase-1 pathways axis in PbAc-injured rats.ConclusionThis study for the first time investigated the biochemical and molecular mechanisms regarding the effects of CSE treatment on PbAc-induced testicular damage in male rats. CSE showed potential attenuative effect on the testis injury induced by PbAc treatment by targeting JAK2/STAT3, and NLRP3/Caspase-1 pathways. These findings suggest that CSE could be used against the adverse effect of PbAc on male repro-toxicity.